Sistem Presensi Online Berdasarkan Metode Rapid Application Development Menggunakan Block Programming - Agus Cahyo Nugroho (Journal of Applied Computer Science and Technology, 2021)
Today, the millennial generation is increasingly inseparable from gadgets. Most of their time is spent interacting using these gadgets. So that even during lectures, they can be sure that they will continue to interact using these gadgets. When this millennial generation is undergoing lectures in the classroom, usually attendance will be circulated using a paper attendance list and students must sign the paper as proof of class attendance. This often creates problems when there are students who leave their presence through classmates. The solution to this problem is to develop a mobile-based online presence system. The urgent need for an online presence system causes the system to be developed quickly. The suitable method for rapid system development is Rapid Application Development (RAD). This QRCode-based online attendance system has succeeded in overcoming the problem of entrusting presence through classmates.